The Ethics of Animal Shelters, by Valéry Giroux, Kristin Voigt and Angie Pepper - Hyde, B.V.E. (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
In this review of The Ethics of Animal Shelters, I explore the book’s practical and philosophical approach to ethical dilemmas in animal shelters, such as euthanasia and triage. I highlight the book’s relevance to bioethics, despite the limited explicit engagement with the field, and critique its justification of killing healthy animals under nonideal conditions. I call for broader bioethical involvement in shelter ethics and the creation of ethical review boards to support decision-making.